2011
DOI: 10.1007/dcr.0b013e3181fd2948
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Risk for a Permanent Stoma After Low Anterior Resection of the Rectum for Cancer? A Six-Year Follow-Up of a Multicenter Trial

Abstract: One patient of 5 ended up with a permanent stoma after low anterior resection of the rectum for cancer, and half of the patients with a permanent stoma had previous symptomatic anastomotic leakage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
186
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(209 citation statements)
references
References 20 publications
18
186
5
Order By: Relevance
“…However, after correcting for those patients who died or were lost to follow-up before reversal, the 57% rate of stoma reversal remains below the range previously reported. These previous evaluations of stoma reversal have found that receipt of post-operative chemotherapy, 7,10 increasing age, 7 metastatic disease, 8 comorbidities, 7 and perioperative complications, 8,9,11 were associated with non-reversal. Our multivariable results corroborated the influence of older age and greater comorbidity on non-reversal, but we also found male gender (similar to diverticulitis 26 ) and higher income increased a patient's chance of reversal.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…However, after correcting for those patients who died or were lost to follow-up before reversal, the 57% rate of stoma reversal remains below the range previously reported. These previous evaluations of stoma reversal have found that receipt of post-operative chemotherapy, 7,10 increasing age, 7 metastatic disease, 8 comorbidities, 7 and perioperative complications, 8,9,11 were associated with non-reversal. Our multivariable results corroborated the influence of older age and greater comorbidity on non-reversal, but we also found male gender (similar to diverticulitis 26 ) and higher income increased a patient's chance of reversal.…”
Section: Discussionmentioning
confidence: 93%
“…And while we used initial length of stay as a surrogate for immediate postoperative complications, we were unable to identify or adjust for those patients with anastomotic leak or stricture which could significantly influence reversal rates. 11 Finally, we could not reliably distinguish between loop or end stomas based on billing codes, which may significantly influence rates of reversal.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This was followed by a discussion regarding the consequences of leakage, which include a decrease in overall survival and a possible decrease in cancerfree survival. Also discussed, was a Swedish nationwide multicenter randomized control trial (RCT) showing that 56% of patients with symptomatic anastomotic leakage received a permanent stoma [6].…”
Section: Doctor Hans Schardey and Doctor James Fleshman Presentationmentioning
confidence: 99%
“…Positive intraoperative leak tests are addressed during surgery through additional suturing, sealant, re-anastomosis, or diversion and stoma creation [9]. Conversely, leaks identified post-operatively, that cannot be treated with antibiotics, require secondary procedures including percutaneous or surgical draining of abscesses or secondary surgery to correct the leak [6], the need for creation of a permanent stoma is also increased in these cases [10]. Prevention of mortality due to anastomotic leak is largely dependent upon early detection and treatment of leaks [6,11].…”
Section: Introductionmentioning
confidence: 99%